Menolak Pornografi: Memberdayakan Perempuan - Siti Musdah Mulia (Universitas Islam Negeri Mataram, 2006)
When people listen to the word pornography, what they have in their imagination is a sexy woman that can arouse sexual desire. Some people perceive pornography and women are interrelated and unseparable. If pernography is then correlated with moral degradation, consequently women are claimed to be the axis of demoralization. Thus, the problem is how to prevent the women from moral degradation, if needed by limiting their rights through constitution. To support the idea they use religious teachings based on the interpretation of Islamic scholars. Normatively, by intensive observation, it is found out that Quranic verses and the tradition of the Prophet are on the side of women Therefore, pornography cannot be stopped merely by discriminating and limiting the rights of the women. What has to be done is providing the women with knowledge and awareness of sex by strengthening the function of family and giving sex education responsibly.